Impacto da divulgação da pesquisa sobre biocurativos e avaliação psicosocial dos pacientes - Cotrim, Ondina Silvia [UNESP] (2013)
The objective of this article was to analyze the impact of the dissemination of results from scientific research regarding the use of bio bandages for the treatment of patients with chronic wounds which present a difficult therapeutic approach. There was an increase in demand for bio bandages, via e-mail or telephone, after two reports were nationally broadcasted by two television stations. For a period of 10 years, the average of patients who looked for help did not exceed the number of 250 patients a year. However, in the first 10 days subsequent to the reports, 548 e-mails from patients were received. Not to mention the number of requests by phone, which was three times higher than those made by e-mail during the same period. From this fact, it can be inferred the importance of the re-evaluation of the treatment of patients with chronic wounds in the country, with a more systemic view on public health. Patients selected for the clinical protocol had multidisciplinary follow-up and responded to a structured questionnaire from the perspective of a qualitative research. The patients' average profile belongs to B1 social class. Female white patients, with an average age of 63, have had open lesions for a period that vary from six months to 30 years. Male patients practice more sports activities, while female patients are more involved in religious activities and craft work. Most patients have a technological profile; they believe in medicine innovations and are confident in the treatment. It is also the opinion of an expressive majority that the chronic wounds (CW) caused not only a great impact on them, but also in their relatives’ lives. This fact draws attention to the need of having a more comprehensive care in relation to non- chronification.